Differences in stroke and ischemic heart disease mortality by occupation and industry among Japanese working-aged men - Koji Wada; Hisashi Eguchi; David Prieto-Merino (Elsevier, 2016)
Occupation- and industry-based risks for stroke and ischemic heart disease may vary among Japanese working-aged men. We examined the differences in mortality rates between stroke and ischemic heart disease by occupation and industry among employed Japanese men aged 25-59 years. In 2010, we obtained occupation- and industry-specific vital statistics data from the Japanese Ministry of Health, Labour, and Welfare dataset. We analyzed data for Japanese men who were aged 25-59 years in 2010, grouped in 5-year age intervals. We estimated the mortality rates of stroke and ischemic heart disease in each age group for occupation and industry categories as defined in the national census. We did not have detailed individual-level variables. We used the number of employees in 2010 as the denominator and the number of events as the numerator, assuming a Poisson distribution. We conducted separate regression models to estimate the incident relative risk for stroke and ischemic heart disease for each category compared with the reference categories "sales" (occupation) and "wholesale and retail" (industry). When compared with the reference groups, we found that occupations and industries with a relatively higher risk of stroke and ischemic heart disease were: service, administrative and managerial, agriculture and fisheries, construction and mining, electricity and gas, transport, and professional and engineering. This suggests there are occupation- and industry-based mortality risk differences of stroke and ischemic heart disease for Japanese working-aged men. These differences in risk might be explained to factors associated with specific occupations or industries, such as lifestyles or work styles, which should be explored in further research. The mortality risk differences of stroke and ischemic heart disease shown in the present study may reflect an excessive risk of Karoshi (death from overwork). Keywords: Occupation, Industry, Mortality, Ischemic heart disease, Stroke, Japan